Salmonella Impairs RILP Recruitment to Rab7 during Maturation of Invasion Vacuoles - Harrison, Rene E. (The American Society for Cell Biology, 2004)
After invasion of epithelial cells, Salmonella enterica Typhimurium resides within membrane-bound vacuoles where it survives and replicates. Like endocytic vesicles, the Salmonella-containing vacuoles (SCVs) undergo a maturation process that involves sequential acquisition of Rab5 and Rab7 and displacement toward the microtubule-organizing center. However, SCVs fail to merge with lysosomes and instead develop subsequently into a filamentous network that extends toward the cell periphery. We found that the initial centripetal displacement of the SCV is due to recruitment by Rab7 of Rab7-interacting lysosomal protein (RILP), an effector protein that can simultaneously associate with the dynein motor complex. Unlike the early SCVs, the Salmonella-induced filaments (Sifs) formed later are devoid of RILP and dynein, despite the presence of active Rab7 on their membranes. Kinesin seems to be involved in the elongation of Sifs. SifA, a secreted effector of Salmonella, was found to be at least partly responsible for uncoupling Rab7 from RILP in Sifs and in vitro experiments suggest that SifA may exert this effect by interacting with Rab7. We propose that, by disengaging RILP from Rab7, SifA enables the centrifugal extension of tubules from the Salmonella-containing vacuoles, thereby providing additional protected space for bacterial replication.